Implementasi Nilai-Nilai Islam dalam Pendidikan Jasmani dan Olahraga untuk Membentuk Karakter Ulul Albab - Sitti Hasnah; Nugroho Susanto; Syafruddin Syahrudin; Moh. Solehuddin; Elsa Yuniarti; Irawan irawan (At-Ta'dib, 2023)
This study aims to analyze and discuss the implementation of Islamic values in physical education and sports to foster the character of Ulul Albab. The research methodology employed in this study is a literature review, where relevant literature regarding the implementation of Islamic values in physical education and sports, as well as the character development of Ulul Albab, is collected and analyzed. The findings reveal that physical education and sports can serve as effective platforms for shaping the character of Ulul Albab by integrating Islamic values into every sporting activity. Islamic values such as honesty, discipline, hard work, and responsibility can be effectively incorporated into sports activities as means to cultivate strong character traits. Thus, the implementation of Islamic values in physical education and sports can be considered as an alternative strategy in shaping the character of Ulul Albab, individuals who possess good Islamic morality and ethics. In conclusion, this study emphasizes the significance of implementing Islamic values in physical education and sports as a means to enhance the quality and moral character of Ulul Albab.